A Path to Empire: Formation of the Art Culture at the Russian Court of Peter the Great. Ceremonies, Regalia, Jewels by Ekaterina Tyukhmeneva and Julia Bykova (Мoscow, ByksMArt, 2022. 448 p., in Russian): A Book Review - Skvortcova, Ekaterina A. (Actual Problems of Theory and History of Art, 2023)
A fundamental A Path to Empire: Formation of the Art Culture at the Russian Court of Peter the Great (2022) by Ekaterina Tyukhmeneva and Julia Bykova is a breakthrough in studies of the theme and will forever remain an unageing classics. This is the first comprehensive reconstruction of the material world of court ceremonies in the first quarter of the 18th century which addresses equally saved and lost objects and includes all possible aspects — festive decoration of interiors, cathedrals and streets on the most important occasions, regalia, signs of personal glory, and jewelry. On the basis of scrupulous research in Russian and foreign archives, the authors have collected exclusively important material which is valuable not only in itself, but which also offers a key to the dating and attribution of the portraits, while the clarification of the questions of terminology of jewelry enables their correct description.